Mediating 'School Direct': The enactment of a reform policy by university‐based teacher educators in England. (6th March 2020) - Ellis, Viv; Spendlove, David
Abstract : The period 2010 to 2014 is widely acknowledged as a time of highly significant education reform in England, including of Initial Teacher Education (ITE). The Conservative–Liberal Democrat coalition government introduced a programme of 'school‐led' education policies, of which 'School Direct' was intended to shift the balance of power, resources and modes of training teachers away from universities towards schools. Through an analysis of interviews with leaders of ITE in universities in two English regions, we examine the mediations of the School Direct policy from a socio‐cognitive and activity‐theoretical perspective. We identify three emotional frames for perceiving School Direct within the policy environment, drawing on the Vygotskian concept of perezhivanie . We also identify two policy enactment activities that involved bargaining within and rebrokering relationships between universities and schools. Consequently, we argue that the mediations of School Direct reported by the university leaders in our sample can be understood as limited appropriations of the policy within a highly charged emotional context where institutional risks were felt to be ever‐present. We conclude that these leaders did not believe that School Direct achieved a transformation of ITE on the basis of a reconceptualisation of existing practices. The article contributes both to the scant research literature on School Direct as a significant reform by studying university leaders' accounts of policy mediation and the socio‐cognitively informed literature on policy enactment by foregrounding the emotional‐affective dimension of sense‐making.